THE STUDY OF THE WORK OF THE MUSCLES RESPONSIBLE FOR THE FUNCTIONALITY OF THE HIP JOINT AFTER TOTAL HIP ARTHROPLASTY USING DIFFERENT SURGICAL APPROACHES - Bondarenko, Stanislav; Sereda, Dmytro; Karpinska, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Muscles that can be damaged during endoprosthesis are indicated. Objective. To study the features of muscle work to ensure walking function after hip arthroplasty depending on the surgical approach. Methods. The basis of the simulation is the basic OpenSim Gate2392 model. Six models were created that predicted the condition of the muscles of the lower limb in normal conditions, during coxarthrosis and after 6 and 12 months. after surgery with lateral and anterior approaches. The results. For lateral access in 6 months. after the operation, the adductor muscles responsible for stabilizing the pelvis in the single-support phase of the step and during the transfer of the foot do not work enough, while the hip flexor muscles (in the model, the rectus femoris muscle) take over the responsibility for the step, but with overvoltage. On the contrary, with the front approach, we observe a weakening of the flexor muscles, which leads to overstrain of the gluteal muscles and hip stabilizer muscles. After 12 months, the muscle strength normalizes for most of them to 90–95 % of the norm, a 2–3 times increase in the torque of the hip flexor muscles and hip stabilizer muscles is observed. Taking a normal step causes muscle strain. During the anterior approach, the foot is transferred during the phase, that is, when most of the muscles are involved. The rectus femoris muscle, which is the strongest of the muscles discussed in the paper, does the main work of moving the foot. In the case of possible damage to the rectus muscle during anterior access, even after a year there is a violation of its work — excessive overexertion and involvement of the reserves of other muscles. Conclusions. Mathematical modeling of the work of muscles that may be damaged during hip arthroplasty surgery, conditional muscle strength for 6 months. after the operation, they are not able to develop the necessary torque to take a normal step. For muscle strength, which in the model corresponded to 12 months, the muscles are able to perform a normal function regardless of surgical access, but their overstrain is observed.